2005
DOI: 10.1002/ajh.20405
|View full text |Cite
|
Sign up to set email alerts
|

Acquired factor VIII inhibitor in patients with hepatitis C virus infection and the role of interferon-α: A case report

Abstract: A patient with HIV and hepatitis C virus (HCV) co-infection developed an autoantibody to factor VIII after 8.7 months of treatment with pegylated interferon-a and ribavirin. Three previous cases of the development of factor VIII autoantibody in patients infected with the hepatitis C virus have been reported. Only one of these patients was treated with interferona, and this patient had hemophilia A, a condition prone to development of factor VIII autoantibody, even without interferon treatment. It is possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
(32 reference statements)
0
19
0
1
Order By: Relevance
“…The development of inhibitors in association with antiviral therapy for chronic hepatitis C is poorly understood. Schreiber and Bräu proposed that the presence of anti‐FVIII autoantibodies in hepatitis C infection was, in some cases, extrahepatic autoimmune manifestations similar to cryoglobulinemia and hepatitis‐induced thrombocytopenia . Otherwise, a large retrospective study that analysed surveillance data collected on 7386 American males with severe haemophilia A over a 13‐year period did not found association between inhibitor development and HCV infection .…”
Section: Discussionmentioning
confidence: 78%
“…The development of inhibitors in association with antiviral therapy for chronic hepatitis C is poorly understood. Schreiber and Bräu proposed that the presence of anti‐FVIII autoantibodies in hepatitis C infection was, in some cases, extrahepatic autoimmune manifestations similar to cryoglobulinemia and hepatitis‐induced thrombocytopenia . Otherwise, a large retrospective study that analysed surveillance data collected on 7386 American males with severe haemophilia A over a 13‐year period did not found association between inhibitor development and HCV infection .…”
Section: Discussionmentioning
confidence: 78%
“…Several reviews have shown that both solid tumors and hematologic malignancies can cause this phenomenon, with lung and prostate adenocarcinoma and low grade lymphoproliferative diseases being the most common culprits [17–22]. Although there have been several case reports describing patients with HCV who developed acquired FVIII inhibitors, most of these patients were undergoing treatment with interferon, a known immunomodulatory agent [2428]. Schreiber and Bräu proposed that the presence of autoantibodies to FVIII in HCV was in fact extrahepatic autoimmune manifestations similar to cryoglobulinemia and hepatitis-induced thrombocytopenia [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several case reports describing patients with HCV who developed acquired FVIII inhibitors, most of these patients were undergoing treatment with interferon, a known immunomodulatory agent [2428]. Schreiber and Bräu proposed that the presence of autoantibodies to FVIII in HCV was in fact extrahepatic autoimmune manifestations similar to cryoglobulinemia and hepatitis-induced thrombocytopenia [24]. There have been several case reports associating inhibitors with HIV, but these were all seen in patients receiving HAART and were attributed to IRIS [2832].…”
Section: Discussionmentioning
confidence: 99%
“…Certain medications such as penicillins, sulfa drugs and phenytoin have been reported as causes of acquired haemophilia [3]. Interferon‐α use in a non‐haemophilic patient with chronic hepatitis C infection has been reported to be an extremely rare cause of this presentation [2,4]. HCV could itself be associated with autoimmune manifestations including haematological side effects like mixed cryoglobulinemia, thrombocytopenia and generation of autoantibodies like antinuclear antibody, rheumatoid factor, antismooth muscle cell, anticardiolipin and antithyroglobulin antibodies [5].…”
Section: Discussionmentioning
confidence: 99%